Allyship in disability arts: roles, relationships, and practices. Issue 2 (2nd April 2020) - Hadley, Bree
ABSTRACT: In this article, I propose that investigation of allies, ally skills, and allyship in disability arts is overdue. I articulate some of ways in which non-arts approaches to allyship need to be adapted to meet the needs of disabled artists, given the aesthetic as well as professional and social dimensions of allyship distinctive to disability arts. In doing so, I highlight the need for new theory, terminology, and frameworks to define the different approaches to allyship, developed by different artsworkers, operating in different roles, across the different domains of disability arts and/or arts and disability practice.